Transparency in Revenues from Artisanal and Small-Scale Mining of Tin, Tantalum, Tungsten and Gold in Burundi - World Bank Group (World Bank, Washington, DC, 2016)
Burundi has a wide range of mineral deposits of which tin, tantalum and tungsten ores, along with gold, are its primary mineral exports. Burundi’s geological endowment also includes nickel, rare earths, vanadium, and construction materials. The majority of mineral extraction is carried out by artisanal and small-scale mining (ASM) which is officially structured through cooperatives. Tin, tantalum, tungsten (from the minerals cassiterite, tantalite and wolframite and often referred to as the ‘3Ts’) and gold are the primary minerals mined and exported. Improvements in the gold sector are where the Burundian Government stands to make the greatest gains though this is complex to achieve and needs a very practical strategy which is grounded in market and trade realities. Taxation is one element of this but should not be considered in isolation. Engagement with the existing market and finding incentives for formalization is essential. The Government of Burundi should showcase its efforts to improve transparency and traceability. The next step will be to use EITI and iTSCi standards to help to meet the basic needs of artisanal mining communities and to contribute to formalization. This will promote positive perceptions and acceptance of both systems to the benefit of Burundi’s mineral sector and national revenues.